Combined Ultrasound and Microwave Food Processing: Efficiency Review - Leonid Ch. Burak; Andrey P. Zavaley (Техника и технология пищевых производств)
Modern methods of food processing combine ultrasonic and microwave treatment. This article reviews scientific publications on combined microwave and ultrasound technologies in food processing. The review involved standard methods of data analysis and covered 85 Scopus and Web of Science research papers on combined microwave and ultrasonic food treatment published in English in 2010–2023. The article describes the principles and specific features of ultrasonic and microwave food processing methods, their combinations, equipment design, and applications as part of various food processing stages, e.g., defrosting, drying, extraction, sterilization, etc. Microwaves increase the heating rate while ultrasound increases the efficiency of heat and mass transfer. Their combined use reduces processing time, improves product quality, facilitates moisture drainage, and provides uniform heating. The combined effect of microwaves and ultrasound increases the processing efficiency, thus preserving the nutritional value and quality of the final product. Ultrasonic technology serves as an aid to efficient and environmentally-friendly microwave heating, which has a wide range of applications in the food industry. The review can be used in further research in extraction, drying, defrosting, and sterilization. It can help food industry specialists to select optimal food processing methods.